2015
DOI: 10.1038/srep18206
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rearing environment on the development of gut microbiota in tilapia larvae

Abstract: This study explores the effect of rearing environment on water bacterial communities (BC) and the association with those present in the gut of Nile tilapia larvae (Oreochromis niloticus, Linnaeus) grown in either recirculating or active suspension systems. 454 pyrosequencing of PCR-amplified 16S rRNA gene fragments was applied to characterize the composition of water, feed and gut bacteria communities. Observed changes in water BC over time and differences in water BCs between systems were highly correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
215
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(249 citation statements)
references
References 108 publications
(121 reference statements)
23
215
3
8
Order By: Relevance
“…Several management aspects may explain the lack of effects on FCR, such as lower water temperature and dietary protein level, the feeding frequency and the incorporation method of the probiotic. However, different hosts and rearing conditions, with their particular water and gut microbiota (Giatsis et al, 2015), may be sufficient for some unpredictability of the results. In a previous study in rainbow trout, the authors observed a decrease in VFI in fish-fed probiotics when compared with the control group (Ramos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several management aspects may explain the lack of effects on FCR, such as lower water temperature and dietary protein level, the feeding frequency and the incorporation method of the probiotic. However, different hosts and rearing conditions, with their particular water and gut microbiota (Giatsis et al, 2015), may be sufficient for some unpredictability of the results. In a previous study in rainbow trout, the authors observed a decrease in VFI in fish-fed probiotics when compared with the control group (Ramos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have looked at what factors shape and modulate the development of the tilapia gut microbiome (Giatsis et al, 2015, Giatsis et al, 2014. During early ontogenetic stages, while the gut is not fully developed, the effects of environmental factors such as water physicochemical parameters are stronger.…”
Section: Discussionmentioning
confidence: 99%
“…Bakke et al (2013) demonstrated that the gut microbiota of cod larvae is more strongly influenced by microbiota present in the water rather than by the microbiota associated with feed (Bakke et al, 2013). In a previous study, we confirmed a high and consistent correlation between water and gut microbiota of tilapia larvae whereas less than 1% of all OTUs was shared between gut and feed (Giatsis et al, 2015). However, our present results show that bacteria associated to the diet lead to alterations in gut microbiota and that these changes are more pronounced in the sludge-based diets rather than in the control.…”
Section: Discussionsupporting
confidence: 82%
“…However, our present results show that bacteria associated to the diet lead to alterations in gut microbiota and that these changes are more pronounced in the sludge-based diets rather than in the control. Contrarily to previous studies (Bakke et al, 2013;Giatsis et al, 2015), gut shared a much higher number of OTUs with the feed than with the water. However, despite marked…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation